Effect of ultrasonic pretreatment on whey protein hydrolysis by alcalase: Thermodynamic parameters, physicochemical properties and bioactivities. (April 2018) - Wu, Qiongying; Zhang, Xuefen; Jia, Junqiang; Kuang, Cong; Yang, Hongshun
Graphical abstract: Highlights: E a, Δ H and Δ S Values for whey protein enzymolysis were decreased by ultrasound. Ultrasound led to changes in physicochemical properties of whey protein. Bioactivities of whey protein hydrolysates were increased by ultrasound. Ultrasonic pretreatment can improve the efficiency of whey protein hydrolysis. Abstract: The effects of ultrasonic pretreatment on the enzymolysis thermodynamics and physicochemical properties of whey protein, and the mechanisms behind those effects, were investigated. Changes in the angiotensin-I converting enzyme (ACE) inhibitory and immunomodulatory activities of whey protein hydrolysates after ultrasonic pretreatment were also determined. Results showed that the ultrasonicated whey protein had a higher in degree of hydrolysis than the non-sonicated protein. After the pretreatment, the activation energy ( E a ), enthalpy of activation (Δ H ) and entropy of activation (Δ S ) of whey protein enzymolysis were decreased by 15.9%, 16.8%, and 16.4%, respectively. There was no significant change in free energy (Δ G ) ( P > 0.05). Physicochemical analysis revealed that ultrasound had induced unfolding of the whey protein, resulting in a 43.7% increase in its surface free sulfhydryl content and a 62.6% increase in surface hydrophobicity. Ultrasound significantly decreased the protein's α-helical content and significantly increased its β-sheets and β-turns ( P < 0.05). The ACE inhibitory and immunomodulatory activities of the whey protein hydrolysates were significantly increased by ultrasonic pretreatment ( P < 0.05). These results suggest that ultrasound can be applied to enhance whey protein enzymolysis for the generation of novel bioactive peptides that can be used as drug or functional food ingredient.